Using a Handheld Device for Patient Data Collection: A Pilot for Medical Countermeasures Surveillance. (January 2016) - Daley, Matthew F.; Goddard, Kristin; McClung, Melissa; Davidson, Arthur; Weiss, Gretchen; Palen, Ted; Nyirenda, Carsie; Platt, Richard; Courtney, Brooke; Reichman, Marsha E.
Medical countermeasures (MCMs) are medical products used during public health emergencies. This study, conducted within the Mini-Sentinel Initiative, sought to develop the patient identification and matching processes necessary to assess safety outcomes for MCMs. A handheld device was used to collect identifying information (e.g., name, birthdate, and sex) from the driver's licenses of 421 individuals presenting for routine care at their primary care medical office. Overall, 374 individuals (88.8%) could be linked to their electronic health data using driver's license information. The device was also pilot-tested at a seasonal influenza immunization clinic: detailed vaccine information (e.g., lot number and manufacturer) was captured with a high degree of accuracy. This investigation demonstrated that a handheld device is a feasible means of collecting patient identity and medical product receipt data. This capacity should be useful for safety surveillance of MCMs, particularly when dispensed in settings outside the traditional health-care delivery system.